Dense-field spray droplet size quantification of flashing boiling atomization using structured laser illumination planar imaging technique. (1st March 2023) - Qiu, Shuyi; Wang, Shangning; Zhang, Yijia; Li, Xuesong; Hung, David; Xu, Min
Highlights: SLIPI and LIEF/Mie were firstly combined to quantify the droplet size of dense spray. SLIPI-LIEE/Mie methods provide more accuracy droplet sizes distribution dates than LIEF/Mie methods. Flash boiling spray has smaller and more uniformly distributed droplets. There is no liquid core region or sudden droplet size reduction during flash boiling processes. Abstract: The statistics of droplets formed by the primary jet breakup of a liquid atomization system are critical since it determines the atomization quality and resultant spray characteristics. However, quantifying the droplet statistics by applying optical diagnostic instruments is challenging because of the dense population of droplets near the nozzle exit. In a flash boiling spray, the more rapid breakup produces a higher optical dense droplet cloud, which is more challenging. Besides, the interference from the vapor phase heavily evaporated is more problematic. In this study, we incorporated an in-house developed laser-induced exciplex fluorescence (LIEF/Mie) based droplet sizing technique to quantify the near-field droplet characteristics of a single jet flash boiling spray, which can separate the liquid spray from the vapor phase to eliminate the influence of the vaporization. To mitigate the interference of multiple scattering in the dense region, a 3-phase structured laser illumination planar imaging (3p-SLIPI) facility was implemented into the measuring system to modulate the laser beam. The combination of these two unique techniques succeeded in obtaining accurate quantification of a planar droplet size distribution of this flash boiling spray. The 3p-SLIPI-LIEF/Mie measurements were validated against phase Doppler interferometry (PDI) droplet size measurement results. It is found from this study that the SLIPI-LIEF/Mie results are more accurate and more appropriate for simulation or theoretical analysis compared to LIEF/Mie results. The investigation of the flash boiling sprays under various superheat conditions was conducted using this technique. The quantitative near-field droplet size information reveals the prompt atomization mechanism of the flash boiling sprays. Comparing to the non-flash boiling sprays, the SMD is much smaller, the distribution is more uniform, and the tendency becomes more significant as the superheat degree increases. The SLIPI-LIEF/Mie results show that there is no liquid core region or sudden droplet size reduction due to flash boiling secondary micro-explosion breakups. Rather, a central dense region formed due to rapid expansion and evaporation at the exterior zones of the flash boiling spray was found.